2007
DOI: 10.1063/1.2825636
|View full text |Cite
|
Sign up to set email alerts
|

Emission studies on photonic crystals fabricated using dyed polystyrene colloids

Abstract: Three dimensionally ordered photonic crystals are fabricated with rhodamine B dyed polystyrene colloidal spheres using the inward growing self-assembling method in less than 3 h. This avoids the difficulties due to infiltration of active materials into passive photonic crystals. The superior optical quality of the photonic crystals fabricated using this method results in high reflectance values even at large angles of incidence. The study of emission characteristics on these functionalized photonic crystals sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 24 publications
2
18
0
Order By: Relevance
“…Yamasaki et al discussed the emission in dye doped polystyrene (PS) PhC [8]. A similar study was reported by our group for Rhodamine-B dye doped polystyrene (PS-RhB) PhC in 2007 [9]. Li et al reported the stop band effect and spectral narrowing in RhB-doped poly(styrenemethyl methacrylate-acrylic acid) (P(St-MMA-AA)) PhC [10].…”
Section: Introductionsupporting
confidence: 52%
See 2 more Smart Citations
“…Yamasaki et al discussed the emission in dye doped polystyrene (PS) PhC [8]. A similar study was reported by our group for Rhodamine-B dye doped polystyrene (PS-RhB) PhC in 2007 [9]. Li et al reported the stop band effect and spectral narrowing in RhB-doped poly(styrenemethyl methacrylate-acrylic acid) (P(St-MMA-AA)) PhC [10].…”
Section: Introductionsupporting
confidence: 52%
“…The stop band of the crystal has affected different ranges of emission spectrum at different angles. The emission and reflection spectra of this crystal do not overlap at angles larger than 45° [9]. Hence the emission recorded at a larger angle of 60°is considered to be the intrinsic emission of the dye (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The disallowed band of wavelengths in photonic crystals is called the photonic band gap, which is similar to the energy gap of the electrons in the semiconductors. The photonic band gap gives rise to distinct optical phenomena, such as the inhibition of spontaneous emission [1,2], high-reflecting omnidirectional mirrors [3,4], and low-loss-waveguide [5].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the emission intensity and the rate decrease inside the photonic stop gap with the reduction of the LDOS. Inhibition of spontaneous emission of dyes and quantum dots has been observed in self-assembled colloidal photonic crystals [9,[14][15][16][17]. The enhancement of LDOS in the frequency range of the stop gap can be achieved by creating intentional defects that effectively act as cavities with high quality factors in the otherwise periodic structure [2].…”
Section: Introductionmentioning
confidence: 99%